Thực trạng hoạt động phòng, chống bạo lực học đường tại trường trung học phổ thông: Một nghiên cứu tại thành phố Hồ Chí Minh - Lê Hoàng Phương Khanh, Lê Hoàng Phương Khanh; Nguyễn Thị Quốc Minh, Nguyễn Thị Quốc Minh (Tạp chí Giáo dục, 2026)
School violence has become one of the most concerning social issues in the educational environment, particularly in high schools located in major urban areas such as Ho Chi Minh City. This study analyzes the current situation of school violence prevention and control through surveys conducted at Tran Hung Dao High School and Go Vap High School. The findings indicate that although efforts in preventing and controlling school violence have received significant attention with the overall average scores across criteria rated as “Good” - there remain limitations in the coordination among internal and external stakeholders involved in the prevention and intervention process. The research serves as a call to action for high schools to enhance awareness education, develop coping skills, strengthen communication and schoolbased campaigns, establish multidimensional collaboration mechanisms, and build a safe, healthy, and friendly learning environment.